Kosmologi Hindu Dalam Konsep Purusa Dan Pradhana Pada Palinggih Kiwa Tengen Di Pura Besakih - Komang Pusparani; I Nyoman Temon Astawa; Luh Kadek Dwi Utami; Dewa Agung Putri Dwijayanti (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
Hindu cosmology in Palinggih Kiwa Tengen, is an element of balance in the worship of Ida Sang Hyang Widhi Wasa as the almighty power of the universe in terms of making a balance of life in the world and the hereafter. The teachings of this religion as a source of life balance and continuity of mind and body. Furthermore, there are elements of the union of the Great Bhuwana and in Bhuwana Alit and their contents all were created by God, beginning with Sunia Loka with two elements namely Purusa and Pradhana. This Hindu cosmology can better understand the concept of the creation of the universe or universe. In the concept of temples in form and the structure of temples with seven levels or mandalas is a reflection of the creation of this world.